2017
DOI: 10.4269/ajtmh.17-0254
|View full text |Cite
|
Sign up to set email alerts
|

Plasmodium vivax Infections over 3 Years in Duffy Blood Group Negative Malians in Bandiagara, Mali

Abstract: was thought to infect only the erythrocytes of Duffy blood group positive people. In the last decade, has appeared throughout Africa, both in areas where Duffy positive and negative people live side by side as in Madagascar and Ethiopia and in areas where people are primarily Duffy negative, such as in western Kenya. We performed quantitative polymerase chain reaction on blood samples dried onto filter paper to determine the prevalence of and in a cohort of 300 children (newborn to 6 years of age) in Bandiagar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
75
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 60 publications
(76 citation statements)
references
References 41 publications
(66 reference statements)
0
75
0
1
Order By: Relevance
“…This discovery led to further functional studies that identified the P. vivax Duffy-binding protein (PvDBP) that is crucial for RBC invasion (Miller et al 1979;Haynes et al 1988;Wertheimer and Barnwell 1989;Chitnis and Miller 1994), which is now undergoing clinical trials as a vaccine candidate (Chitnis and Sharma 2008;Mueller, Shakri, and Chitnis 2015). Cases of P. vivax infection in FY*ES individuals have more recently been reported (Ryan et al 2006;Menard et al 2010;Ngassa Mbenda and Das 2014;Lo et al 2015;Abdelraheem et al 2016;Niangaly et al 2017). Functional work leading to the discovery of transferrin receptor 1 (TfR1) as an important alternative receptor for P. vivax recognition and invasion of RBCs could explain these cases (Gruszczyk et al 2018).…”
Section: Functional Validation Of Malaria-protective Genesmentioning
confidence: 99%
“…This discovery led to further functional studies that identified the P. vivax Duffy-binding protein (PvDBP) that is crucial for RBC invasion (Miller et al 1979;Haynes et al 1988;Wertheimer and Barnwell 1989;Chitnis and Miller 1994), which is now undergoing clinical trials as a vaccine candidate (Chitnis and Sharma 2008;Mueller, Shakri, and Chitnis 2015). Cases of P. vivax infection in FY*ES individuals have more recently been reported (Ryan et al 2006;Menard et al 2010;Ngassa Mbenda and Das 2014;Lo et al 2015;Abdelraheem et al 2016;Niangaly et al 2017). Functional work leading to the discovery of transferrin receptor 1 (TfR1) as an important alternative receptor for P. vivax recognition and invasion of RBCs could explain these cases (Gruszczyk et al 2018).…”
Section: Functional Validation Of Malaria-protective Genesmentioning
confidence: 99%
“…A detailed description of the study site can be found elsewhere (7). In addition, Duffy blood group negative subjects were observed to be persistently infected by P. vivax (8) .…”
Section: Study Areamentioning
confidence: 99%
“…The distribution of P. vivax in Duffy-negative individuals is unusual in Africa and may mirror the distribution of other P. vivax ligands. For example, in Mali, P. vivax infections in Duffy-negative individuals are limited to around 2% frequency and only in the northern part of the country, near the Sahel (13). In contrast, in central Mali near Bamako, no P. vivax infections were identified in hundreds of people tested with sensitive molecular diagnostics for P. vivax.…”
Section: Differential Expression Of Different Family Members In P Vivaxmentioning
confidence: 99%
“…However, Duffy-negative individuals have been diagnosed with P. vivax infections throughout Africa (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23), in part, because of the development of a sensitive real-time PCR test for P. vivax.…”
mentioning
confidence: 99%